Perceived usability evaluation of Google Classroom, Drive and Meet in the teaching and learning process at the Universidad Nacional de San Antonio Abad del Cusco during the COVID-19 pandemic - Gamarra Salas, Jisbaj (2021)
Peru, like the rest of the world, has been affected in many ways by the COVID -19. The education sector was not immune to this situation. Face-to-face classes at all levels of education were canceled, education had to migrate to virtual classes. In this context, virtual educational applications took a more significant role in the teaching and learning processes, usability a critical attribute that must be considered in this platform. This research aims to measure the usability of the leading educational virtual applications currently used by the National University of San Antonio Abad del Cusco in its teaching and learning process: Google Classroom, Google Drive, and Google Meet. The study has a quantitative approach and descriptive scope with non-probabilistic sampling. To measure the usability of these applications, the System Usability Score (SUS) questionnaire was applied to an approximate population of 1150 teachers and 19 000 students, of which a total of 211 participants, 137 students, and 74 teachers responded. The study results show that the perceived usability for the three applications, in general, is good for all the participants (SUS score 69,85). The usability analyzed in detail is very good for teachers, and learning is ideal for both. In this sense, considering the context of the global pandemic, Google tools are convenient to quickly adapt to the teaching process in the virtual environment, and these tools are easy to use and learn.